NFATc1 Expression as a Prognosticator in Urothelial Carcinoma of the Upper Urinary Tract - Takashi Kawahara; Satoshi Inoue; Kazutoshi Fujita; Taichi Mizushima; Hiroki Ide; Seiji Yamaguchi; Hiroaki Fushimi; Norio Nonomura; Hiroshi Miyamoto (Translational Oncology, 2017)
We recently found that NFATc1, a member of the NFAT family and a key regulator of the immune response, could induce bladder carcinogenesis and cancer progression. In this study, we immunohistochemically stained for NFATc1 in upper urinary tract urothelial carcinoma (UUTUC) specimens and paired nonneoplastic urothelial tissues. NFATc1 was positive in 51 [52%; 40 (40%) weak (1+), 9 (9%) moderate (2+), and 2 (2%) strong (3+)] of 99 UUTUCs, which was significantly higher than in benign urothelium [30 (36%) of 83; 28 (34%) weak and 2 (2%) moderate] (0 vs 1+/2+/3+, P = .038; 0/1+ vs 2+/3+, P = .023). There were no significant associations between NFATc1 expression pattern and tumor grade or pT stage. However, the positive rates of NFATc1 expression tended to be higher in renal pelvic tumors (60%) than in ureteral tumors (42%; P = .080) as well as in pN+ tumors (75%) than in pN0 tumors (49%; P = .089). Kaplan-Meier and log-rank tests revealed that moderate (2+) to strong (3+) NFATc1 expression correlated with lower progression-free survival (P = .032) and cancer-specific survival (P = .005) rates in the 99 cases. Patients with high (2+/3+) NFATc1 muscle-invasive tumor (n = 9) also had a significantly higher risk of cancer-specific mortality (P = .021) compared to those with low (0/1+) NFATc1 muscle-invasive tumor (n = 53). Thus, compared with nonneoplastic urothelium, a significant increase in the expression of NFATc1 in UUTUC was seen, implying the involvement of NFATc1 signals in the development of UUTUC. The current results further suggest that NFATc1 overexpression serves as a predictor of poor prognosis in patients with UUTUC.